Updates in the Management of Merkel Cell Carcinoma - Divino, Paulo Henrique do Amor; Souza, Gabriel Passos; Ribeiro, Maurício Fernando Silva-Almeida; Horta, George; Silveira-Lima, Fabíola Ambrosio; Real-Salgues, Alessandra Corte; Munhoz, Rodrigo Ramella (Brazilian Journal of Oncology, 2019)
Merkel cell carcinomas are rare cutaneous malignancies with neuroendocrine features that affect elderly individuals with a history of chronic sun exposure and immunosuppression. More recently, a human viral pathogen, the Merkel cell polyomavirus, has been implicated in the carcinogenesis of this disease. Its particularly aggressive biological behavior, the delay in diagnosis related to the lack of awareness, as well as the paucity of effective therapeutic modalities have historically contributed to the high lethality and dismal prognosis. Although surgery and radiation therapy remain the therapeutic pillars for patients with localized disease, the recognition of its immunogenic potential, with the consequent development and successful implementation of immune checkpoint blockade for those with advanced disease has significantly changed the treatment landscape for these patients. In this review, etiopathogenic, diagnostic and therapeutic aspects related to Merkel cell carcinomas are thoroughly addressed.
Keywords: neuroendocrine tumors; polyomavirus; immunotherapy; Carcinoma; Merkel Cell